Off-Label Drug Use in Pediatric Practice: Unsolved Problems - A. R. Titova; I. L. Asetskaya; S. K. Zyryanov; V. A. Polivanov (Union of pediatricians of Russia, 2015)
The widespread «off-label» drug use and the prescribing of unlicensed medicines in pediatric practice is a major health problem. The authors discuss actual regulatory and legal issues of «off-label» drug use in children in the US, Europe and Russia. The results of different population-based studies from many countries, showing the structure and frequency of «off-label» drug use in children, are summarized in this article. It is shown that such practice increases the risk of adverse drug reactions. The authors offer practical recommendations for a safer use of drugs in pediatric practice. The priority issue is conducting high quality clinical trials with the participation of children, improving national pharmacovigilance and the monitoring of off-label drug use, developing pediatric formularies, improving doctors' knowledge and awareness of safety and efficacy of medicines in pediatric population.